ENGLISH EQUIVALENT TRANSLATIONS FOR SUFFIX -NYA - Afrianto Afrianto; Redika Cindra Reranta (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2019)
Suffix-nya is one of suffixes in Bahasa Indonesia which has various functions. Those varieties cause various forms of equivalent translation in English. Thus, this research aims at investigating the equivalent translation of suffix-nya and its functions. Applying documentary research, the researchers gathered the data in form of Indonesian sentence consisting suffix-nya and its translation from a novel Laskar Pelangi and its English version The Rainbow Troops. Further, this research was conducted under the qualitative method. The result of the analysis shows various equivalent translations and their functions. It is finally reported that the suffix-nya has six alternative equivalent translations; they are pronoun (his, her, their, its, he, his, her, them, and it), apostrophe (-‘s), article (the), demonstrative (this), adverb (-ly), and verb (modal + auxiliary: would be and should have, copular verb; seem). Other than the equivalents, there are seven functions found; they are possessive marker, objective pronoun, subjective pronoun, definite article, deictic marker, adverbial former, and predicate. Dealing with the context of sentences or discourse and understanding it helps to decide the best equivalent translation for suffix –nya which is pertained to a particular constituent of the sentences.Keywords: context, equivalent translation, function of the equivalence, suffix -nya PADANAN BAHASA INGGRIS UNTUK SUFIKS -NYAAbstrakSufiks –nya merupakan salah satu bentuk sufiks dalam bahasa Indonesia yang memiliki beragam fungsi. Ragam fungsi tersebut memunculkan beberapa bentuk terjemahan dalam bahasa Inggris. Berkenaan dengan hal tersebut, penelitian ini menilik padanan dan fungsi sufiks –nya. Sejalan dengan menerapkan analisis dokumen, data dikumpulkan dalam bentuk kalimat yang memiliki sufiks –nya dalam novel Laskar Pelangi dan terjemahan kalimat tersebut dalam novel The Rainbow Troops. Lebih jauh, metode kualitatif diaplikasikan dalam penelitian ini. Berdasarkan hasil analisis, dapat dilaporkan bahwa terdapat enam bentuk padanan untuk sufiks –nya, yaitu pronomina (his, her, their, its, he, his, her, them, dan it), apostrof (-‘s), artikel (the), demonstratif (this), adverbia (-ly), and verba (modal + kata kerja bantu (auxiliary): would be and should have, verba kopula: seem). Selain padanan tersebut, terdapat tujuh fungsi yang ditemukan, yakni penanda posesif (possessive marker), objektif pronominal, subjektif pronominal, artikel definit (definite article), penanda deiktis (deictic marker), pembentuk adverbia (adverbial former), dan predikat (predicate). Selain itu, dapat disimpulkan bahwa mengaitkan pada konteks kalimat dan memahaminya secara utuh merupakan langkah dalam menentukan dan mencari padanan sufiks –nya yang melekat pada konsituen tertentu dalam kalimat.Kata kunci: fungsi padanan, konteks, padanan, sufiks –nya, terjemahan